Correlation of gene polymorphisms of vascular endothelial growth factor with grade and prognosis of lung cancer - Changjiang Liu; Xuetao Zhou; Zefeng Zhang; Yang Guo (BMC, 2020)
Abstract Background Vascular endothelial growth factor (VEGF) gene is highly polymorphic, and single nucleotide polymorphisms (SNP) of VEGF gene are associate with cancer prognosis. This study aimed to analyze the correlation of VEGF gene polymorphisms with grade and prognosis of lung cancer. Methods A total of 458 Chinese patients with primary lung cancer were enrolled from September 2008 to October 2013. The genotypes of −2578C > A, −1154G > A, − 460 T > C, and + 405G > C were analyzed in white blood cells from patients using polymerase chain reaction based restriction fragment length polymorphism. Results Our data showed that -1154G > A polymorphism was significantly associated with tumor stages, but all four tested VEGF gene polymorphisms had no significant effect on survival. Conclusions VEGF polymorphisms may relate to stage of lung cancer in Chinese population.